Asistencia Médica en el Morir: ¿Hacia dónde va el Derecho Internacional de los Derechos Humanos? - Miró Quesada Gayoso, Josefina; Saldivar Condori, Gabriela Andrea (Pontificia Universidad Católica del Perú, 2025)
In recent years, the debate around legalizing medical assistance in dying (MAID) has gained momentum worldwide. Sociocultural changes, advancements in bioethics, and statements from international organizations have contributed to an increase in the number of countries considering regulating MAID. However, the debate is still characterized by legal tensions between human rights such as the right to life, freedom, privacy, and personal integrity. This article analyzes the current state of International Human Rights Law (IHRL) in relation to the legalization of MAID. It examines the standards established by both regional and universal human rights systems, focusing on the caselaw of the European Court of Human Rights (ECtHR) and the statements issued by oversight bodies. The article aims to respond to what extent MAID is compatible with IHRL and what obligations states have when addressing this issue. Finally, it offers reflections on the criteria that should be considered when legislating this practice.

En los últimos años, el debate sobre la legalización de la muerte médicamente asistida [MMA] ha cobrado impulso a nivel global. Cambios socioculturales, avances en bioética y pronunciamientos de organismos internacionales han generado que cada vez más países consideren su regulación. Sin embargo, el debate sigue marcado por tensiones jurídicas entre derechos humanos como la vida, libertad, vida privada, integridad personal. Este artículo analiza el estado actual del Derecho Internacional de los Derechos Humanos [DIDH] en relación con la legalización de la MMA. Para ello, examina los estándares desarrollados en los sistemas regionales y universal de derechos humanos, con especial atención a la jurisprudencia del Tribunal Europeo de Derechos Humanos [TEDH] y los pronunciamientos de organismos de supervisión. Busca responder en qué medida la MMA es compatible con el DIDH y qué obligaciones tienen los Estados si deciden regularla. Finalmente, se presentan reflexiones sobre los criterios que deben considerarse al legislar esta práctica.
Medical Assistance in Dying: Where Is International Human Rights Law Heading?
Keywords: Medical Assistance in Dying; Euthanasia; Assisted Suicide; Right to die with dignity; Life with dignity; International Human Rights Law; European Court of Human Rights; Muerte médicamente asistida; Eutanasia; Suicidio asistido; Derecho a una muerte digna; Vida digna; Derecho Internacional de los Derechos Humanos; Tribunal Europeo de Derechos Humanos; https://purl.org/pe-repo/ocde/ford#5.05.00